Take automatic cleaning device's rotary dryer - XU GUIQIAN; LU SHAOFEI; WU XUEZHONG; ZHANG QIANG; LI XIAOFEI (2017)
The utility model relates to a desiccator field, in particular to take automatic cleaning device's rotary dryer. A take automatic cleaning device's rotary dryer, includes dryer cylinder, both ends are connected with the desiccator rotation axis about dryer cylinder, the setting of desiccator rotation axis is fixed on the support frame and with the pivot of motor, the motor setting on the support frame, the last into discharge gate that is provided with of dryer cylinder, the correspondence of dryer cylinder surface is provided with intake pipe and outlet duct, the intake pipe sets up a plurality of automatic cleaning device inside stretching into dryer cylinder on the dryer cylinder inner wall, the utility model discloses novel structure can automatic clear up adnexed dry material on the desiccator inner wall, and it has sufficient space to hold by dry material to ensure that the desiccator is inside to promote the productivity effect. 本实用新型涉及干燥机领域，特别涉及种带自动清理装置的回转干燥机。种带自动清理装置的回转干燥机，包括干燥机筒体，干燥机筒体左右两端与干燥机旋转轴连接，